Systematic review: impact of liver transplantation on employment. (9th March 2018) - Waclawski, E R; Noone, P
Abstract: Background: The majority of liver transplant recipients survive long term after the procedure. Aim: To assess if this positive outcome is associated with improved employment post-transplant. Methods: A systematic review of publications between 2001 and 2016 was performed. A standard procedure was used to search for suitable publications from two databases (PubMed and EMBASE). Duplicates were removed and abstracts screened by both authors for possible inclusion. Possible suitable publications were obtained and examined for the presence of pre- and post-employment information. Full articles that had this information were reviewed by standard methodology for assessment of bias. Results: A total of 162 individual abstracts were screened. Thirty-five full papers were reviewed and 13 papers included in the detailed review. Risk of bias was considered high due to low response rates, poor assessment of prognostic and confounding factors and varying definitions of employment. Heterogeneous data precluded meta-analysis. Eight studies focused on return to work as a primary outcome and five on quality of life with employment as a secondary outcome. Follow-up varied between 2 and 13 years. Rates of employment fell in all studies assessed. Employment rates ranged from 26 to 80% pre-transplant and 18 to 44% post-transplant. The proportion of those categorized as ill-health retired was 24% greater after orthotopic liver transplantation. Conclusions: Improved survival after liver transplantation was not reflected in a return to employment and retirement was common. Areas for further study include interventions to minimize physical deconditioning, depression associated with lower employment rates and type of work available after transplant.